2017
DOI: 10.3906/sag-1609-33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole blood viscosity and plasma NOx on cardiac function and cerebral blood flow in children with chronic kidney disease

Abstract: IntroductionWhole blood viscosity (WBV) is increasingly recognized as a factor implicated in the genesis of atherosclerosis and the progression of vascular disease, such as chronic kidney disease (CKD), in high-risk patients. The principal determinants of WBV are hematocrit, red blood cell deformability, and the viscosity of plasma. Changes in whole blood viscoelasticity are associated with cardiovascular and cerebrovascular complications among patients with CKD, especially in the fifth stage (1-3). Mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The amount of total protein consisting of albumin, fibrinogen and globulins are the most important serum elements that regulate the plasma viscosity. [25][26][27][28] In the study of Briley et al it was found that non-albumin serum proteins were higher in cases with the higher grade of SEC in patients with acute stroke. 29 Globulins, which consist of structures such as carrier protein and antibodies together with fibrinogen, constitute 40% of blood plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of total protein consisting of albumin, fibrinogen and globulins are the most important serum elements that regulate the plasma viscosity. [25][26][27][28] In the study of Briley et al it was found that non-albumin serum proteins were higher in cases with the higher grade of SEC in patients with acute stroke. 29 Globulins, which consist of structures such as carrier protein and antibodies together with fibrinogen, constitute 40% of blood plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Low hematocrit, total protein and albumin values in patients with chronic kidney disease lead to significantly lower blood viscosity levels [ 3 ]. In a study by Canaud et al, blood viscosity increased significantly after hemodiafiltration across the entire shear rate spectrum (from 24.86 to 33.41 when the shear rate was 0.15 s; from 12.75 to 17.25 when the shear rate was 0.94 s; from 3.73 to 4.65 when the shear rate was 128 s) [ 4 ].…”
Section: Editorialmentioning
confidence: 99%
“…Fibrinogen activates RBC membrane integrinαvβ3 receptors resulting in the activation of RBCs aggregation with subsequent development of HVS [ 50 ]. As well, hypoalbuminemia is linked with increasing of blood viscosity and development of HVS [ 52 ]. Serum albumin is inversely correlated with D-dimer and CRP, and hypoalbuminemia is associated with an increased risk of development of coagulopathy in COVID-19 patients by a reduction in the anticoagulant and antiplatelet effects of albumin [ 53 ].…”
Section: Hyperviscosity Syndrome and Covid-19mentioning
confidence: 99%